Jellyfish collagen matrices conserve the chondrogenic phenotype in two‐ and three‐dimensional collagen matrices. (29th January 2015) - Sewing, Judith; Klinger, Matthias; Notbohm, Holger
Abstract: Cartilage is a tissue with a very low capability of self‐repair and the search for suitable materials supporting the chondrogenic phenotype and thus avoiding fibrotic dedifferentiation for matrix‐associated chondrocyte transplantation (MACI) is ongoing. Jellyfish collagen was thought to be a suitable material mainly because of its good availability and easy handling. Collagen was extracted from jellyfish Rhopilema esculentum and the spreading of porcine chondrocytes on two (2D) and three dimensional (3D) collagen matrices examined in comparison with vertebrate collagens, placenta collagen and a commercially available matrix from porcine collagen type I (Optimaix®). In 2D, most chondrocytes kept their round shape on jellyfish collagen and vertebrate collagen type II compared with vertebrate collagen type I. This was also confirmed in 3D experiments, where chondrocytes preserved their phenotype on jellyfish collagen, as indicated by high collagen II/(II + I) ratios (≥54 % and ~92 % collagen type II in mRNA and protein, respectively) and no proliferation during 28 days of cultivation. These observations were discussed with a view to potential structural differences of jellyfish collagen, which might influence the integrin‐mediated adhesion mechanisms of vertebrate cells on jellyfish collagen. This probably results from a lack of integrin‐binding sites and the existence of an alternative binding mechanism such that cells kept their round shape on jellyfish collagen, preventing chondrocytes from dedifferentiation. Thus, collagen from R . esculentum is a very suitable and promising material for cartilage tissue engineering. Copyright © 2015 John Wiley & Sons, Ltd.